MORPHOGENESIS OF THE MOLAR OCCLUSIAL SURFACE OF THE ALLOPHAIOMYS AND PROLAGURUS IS EVOLUTIONAL BASIS OF STRATIFICATION OF EUROPEAN EOPLEISTOCENE SEDIMENTS - KROKHMAL, A. I. (Institute of Geological Sciences, NAS of Ukraine, 2011)
The time of appearance of new taxons in the composite geological section of Eastern Europe Eopleistocene in the article is brought. Dynamics complication of structure of teeth occlusial surface for the species of Allophaiomys and Prolagurus genus resulted. On the basis of these researches, biochronologic dismemberment of Eopleistocene deposits is conducted. Two faunistic complexes are distinguished, in the complement of which enter six therioassociations and phases of their development. It is shown that European microtheriofaunas containing Allophaiomys cannot be older than the upper part of the Olduvai Subchron.